Living for Today or Tomorrow? Self‐Regulation amidst Proximal or Distal Exercise Outcomes. Issue 2 (26th March 2019) - Evans, M. Blair; Shanahan, Erin; Leith, Scott; Litvak, Noah; Wilson, Anne E.
Abstract : Background: Although health promotion efforts to increase exercise behavior often emphasise long‐term outcomes, sustained action in service of a distal reward is challenging. These studies examined how focusing on the proximal benefits of exercise, compared to distal outcomes or more general outcomes, may strengthen individuals' self‐regulatory self‐efficacy and support physical activity or exercise behavior. Methods: Participants in Study 1 ( N  =   1057 community members) completed an online survey. Participants in Study 2 ( N  =   69 students) and Study 3 ( N  =   107 students) experienced experimental manipulations related to proximal or distal outcomes of exercise, and then completed survey measures. In Study 4, new members at a commercial gym ( N  =   210) completed a survey and had check‐ins recorded over 17 weeks. Results: In Study 1, participants who ranked proximal outcomes of exercise as relatively more important than distal outcomes reported more frequent physical activity. In Studies 2 and 3, participants induced to focus on proximal outcomes reported increased self‐regulatory self‐efficacy. In Study 4, valuing proximal benefits predicted sustained exercise behavior (i.e. check‐ins), particularly when fitness goal adherence felt difficult. Conclusions: Those holding increased proximal outcome beliefs reported more activity and greater efficacy to overcome the barriers that derail exercise.